2017
DOI: 10.1007/s10651-017-0389-8
|View full text |Cite
|
Sign up to set email alerts
|

How well does random forest analysis model deforestation and forest fragmentation in the Brazilian Atlantic forest?

Abstract: We assessed the value of applying random forest analysis (RF) to relating metrics of deforestation (DF) and forest fragmentation (FF) to socioeconomic (SE) and biogeophysical (BGP) factors, in the Brazilian Atlantic Forest of Minas Gerais, Brazil. A vegetation-monitoring project provided land cover maps, from which we derived DF and FF metrics. An ecologic-economical zoning project provided more than 300 SE and BGP factors. We used RF to identify relationships between these sets of variables and compared its p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 64 publications
1
6
0
Order By: Relevance
“…We attributed importance of climate (ET, PR, RO, and SWE) and human water use (irrigated agriculture and population density) to the prediction of lake and wetland surface water area using randomForestSRC regression tree analysis (Ishwaran & Kogalur, ), as a nonparametric measure of variable importance (VIMP). This approach is applicable to ecological systems with typically non‐normal distributions, which most of our variables showed through time (Cutler et al, ; De'ath & Fabricius, ; Zanella, Folkard, Blackburn, & Carvalho, ). RandomForestSRC allowed for a two‐step method of randomization to de‐correlate trees, which decreased variance and bias for a stronger representative model (Zhang & Lu, ).…”
Section: Methodsmentioning
confidence: 99%
“…We attributed importance of climate (ET, PR, RO, and SWE) and human water use (irrigated agriculture and population density) to the prediction of lake and wetland surface water area using randomForestSRC regression tree analysis (Ishwaran & Kogalur, ), as a nonparametric measure of variable importance (VIMP). This approach is applicable to ecological systems with typically non‐normal distributions, which most of our variables showed through time (Cutler et al, ; De'ath & Fabricius, ; Zanella, Folkard, Blackburn, & Carvalho, ). RandomForestSRC allowed for a two‐step method of randomization to de‐correlate trees, which decreased variance and bias for a stronger representative model (Zhang & Lu, ).…”
Section: Methodsmentioning
confidence: 99%
“…latitude, longitude). Therefore, many studies have unsurprisingly identified coordinates as one of the, if not the, most important predictor, such as for tree species distribution (Attorre et al, 2011), monthly precipitation (Jing et al, 2016), deforestation (Zanella et al, 2017), phytoplankton abundance (Roubeix et al, 2016) and explaining the spatial variability of soil organic carbon . According to our results, spatial variable selection would have very likely removed geolocation variables from these studies models.…”
Section: Relevance Of Spatial Variable Selectionmentioning
confidence: 99%
“…Statistical methods are commonly used to analyze the relationship between wetland loss and explanatory variables, such as partial least squares regression, partial correlation analysis, linear correlation, logistic regression, gray correlation, and multiple stepwise regression ( van Asselen et al 2013;Meng et al 2017). Meanwhile, machine learning (e.g., random forest method) methods have gradually been applied in land use change studies (Zanella et al 2017).…”
Section: Introductionmentioning
confidence: 99%